2020
DOI: 10.1080/17441692.2020.1828987
|View full text |Cite
|
Sign up to set email alerts
|

Political distrust and the spread of COVID-19 in Nigeria

Abstract: While studies have explored how health sector corruption, weak healthcare system, large-scale immune compromised population, misinformation and prevalence of highly congested slums contribute to the spread of COVID-19 in Nigeria, they have glossed over the impact of political distrust on the spread of the virus. This study explores the impact of political distrust on the spread of COVID-19 pandemic in Nigeria. The study utilised qualitative dominant mixed methods approach comprising telephone interviews and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 38 publications
7
89
2
1
Order By: Relevance
“…Public distrust in government may lead to a lower level of compliance with government measures and thus, unsuccessful public health interventions. 3 , 5 , 11 , 23 For example, Goldstein and Wiedemann 5 reported that higher political and social trust measures are associated with improvements in compliance with stay-at-home orders in the US. The authors underscored the importance of trust in state capacity and the different levels of trust resulting in asymmetrical compliance, compounded by partisanship behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public distrust in government may lead to a lower level of compliance with government measures and thus, unsuccessful public health interventions. 3 , 5 , 11 , 23 For example, Goldstein and Wiedemann 5 reported that higher political and social trust measures are associated with improvements in compliance with stay-at-home orders in the US. The authors underscored the importance of trust in state capacity and the different levels of trust resulting in asymmetrical compliance, compounded by partisanship behavior.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In Nigeria, large-scale political distrust due to corruption was said to undermine public adherence to government COVID-19 policies. 23 A study by Lalot et al revealed that absence of concern and trust significantly reduce people’s compliance with restrictive government measures put in place in Italian and French cities. 24 This is also consistent with the findings among young Swiss adults.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, trust is one of the important determinants of acceptability [41]. In Nigeria, mistrust of the state and its forms of corruption play a negative role in the acceptance of measures to combat the COVID-19 pandemic [42]especially since in the same West African country and in Egypt, two other studies show that respondents believe that the states are not doing enough to curb the pandemic [16,17]. The ght against Ebola in West Africa has also shown how central the issue of trust is in the acceptability of control strategies [43].…”
Section: Discussionmentioning
confidence: 99%
“…This influence is hypothesized to operate via multiple mechanisms, such as compliance with the law, including tax compliance, and political participation, especially electoral turnout (Dalton, 2004;Lussier, 2016). Indeed, research has shown that high political trust is associated with higher compliance with civic duty and government regulation (Letki, 2007;Tyler, 1990), which most recently manifested during the COVID-19 pandemic (Ezeibe et al, 2020;Devine et al, 2020).…”
Section: Introductionmentioning
confidence: 99%